(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: Pott’s spine is a destructive form of tuberculosis and accounts for approximately half of all cases of musculoskeletal tuberculosis. Spinal Tuberculosis is most often missed due to inadequate sample and lack of clinical history. Most of the Extrapulmonary tuberculosis (EPTB) can be diagnosed by Ziehl Nelson stain (ZN) only, when clinically suspected samples are adequate and optimally stained. We are reporting four case series of spinal tuberculosis diagnosed by ZN stain and confirmed by Bactec MGIT Culture. Material & Methods: These four clinically suspected spinal biopsis were received for ZN stain and MTB culture by MGIT. Results: All the four spinal biopsies were found positive by ZN stain as well as by BacTec MGIT.All the four cases were HIV negative. ESR and CRP of all four cases were raised. Discussion & Conclusion: Spinal tuberculosis can be easily diagnosed by ZN stain in resource constraint lab. Despite its common occurrence and the high frequency of long-term morbidity, there are no straight forward guidelines for the diagnosis and treatment of spinal tuberculosis. Early diagnosis and prompt treatment is necessary to prevent permanent neurological disability and to minimize spinal deformity.